PERANCANGAN ULANG STASIUN KERJA YANG ERGONOMIS DENGAN PENDEKATAN PARTISIPATORI UNTUK MANUFAKTUR SKALA KECIL-MENENGAH DI INDONESIA - Amanda, Prantia; Susanti, Lusi; Zadry , Hilma Raimona (JURNAL REKAYASA SISTEM INDUSTRI, 2025)
PT Tiga Pilar Sakato is a medium-scale manufacturing company that produces iron poles in Indonesia experiencing problems at the painting station. The problem experienced is that the painting station is in an open space so that the production process is hampered if the weather is rainy. Based on observations in the field, it was found that the posture of the workers' bodies was not ergonomic, causing the risk of complaints and musculoskeletal injuries to workers. This study uses a participatory ergonomics method, namely active participation from employees at all levels to implement ergonomics programs in the workplace, in this study developing the application of participatory ergonomics in the workstation design process with a design thinking approach through Focus Group Discussion (FGD). The research flow begins with (1) Preparation stage (2) Observation stage and initial data collection (field study) (3) Evaluation stage of existing work stations with participatory ergonomics (4) Workstation redesign stage (5) Analysis stage and (6) Conclusion and suggestion stage. This study produced a selected design proposal with a spray booth concept that has an operator room with an ergonomic work chair, automatic spray gun, boiler heater to help speed up paint drying and a roller machine to make it easier to rotate the pole when painting. At the design simulation stage, it was seen that the existing ergonomic hazard potential check got a total value of 14 "Dangerous" (Value> 7), after the simulation was carried out for the selected design proposal results, it got a total value of 2 "Safe workplace conditions" (Value <2). This shows that the selected design proposal can reduce musculoskeletal disorder complaints for workers. This study also shows that the participatory ergonomics method based on resource, process and result criteria gets an average value of 4.75 "Good" in the workstation design process. Keywords: Participatory Ergonomics, Design Thinking, Work Station, Painting, Iron Pole..